Relationship among local content policy, indigenous oil firms’ participation and job creation in Nigeria: a theoretical concept - Niran, Adedeji Abdulkabir; Ahmad Sidique, Shaufique Fahmi; Abd Rahman, Azmawani; Law, S. Hook (Journal of Developing Areas, 2015)
The focus of this paper is to explain in more detail the theoretical concept of the relationship among local content policy (LCP), indigenous oil firms' participation and job creation in Nigeria's oil and gas sector. There is no doubt about that "capital-intensivity" of oil and gas sector and that it creates little amount of jobs in the economy. However, it has been argued that if the sector is well managed and regulated, it has potential to create sizable employment. This mounts on the perception that several medium-scaled services often required in stages of production of oil products which may generate many employments. Recently, the motive for job creation in oil and gas sector, particularly for local labours, has led many established oil-producing countries to implement some regulatory policies in their hydrocarbon sectors. One common of such policies is the so-called local content policy (LCP). Generally, the LCP often aims at increasing participation of local oil service companies through which employment opportunities would be created for local workforce. Nigeria, a nascent oil-export country, introduced LCP in its hydrocarbon sector early 2001. The core objective of this policy in Nigeria is not uniquely different from other oil-rich countries where the policy has been practiced. The policy is mainly designed to increase participation of Nigerian indigenous firms for value addition to local economy, especially, in terms of creation of more employments for Nigerian workforce within the sector. Some corpus of studies has described the relationship between LCP and local firms' participation in the oil sector, many of which relied on theory of firm. However, they provide little understanding on how such influence relate to job creation. This paper demonstrates and explains in more detail a theoretical relationship that likely to exist among the LCP, indigenous oil firms' participation and job creation in the oil and gas sector. The focus is not on empirical examination of the effect, rather on explanation of conceptual relationship among these variables, which has seen as an indispensable. In this paper, we infer that there might be a linear link between LCP and indigenous oil firms' participation in the industry. This paper argues that the credence of LCP relies on the amount of job it evolved. However, if interaction between LCP and indigenous firms' participation fails to relate to job creation, then, the focal objective of the policy on value addition, as regard to job creation, may not achieved.